Importance of Fatty Acid Compositions in Patients with Peripheral Arterial Disease - Gautam, Milan (Public Library of Science, 2014)
OBJECTIVE: Importance of fatty acid components and imbalances has emerged in coronary heart disease. In this study, we analyzed fatty acids and ankle-brachial index (ABI) in a Japanese cohort. METHODS: Peripheral arterial disease (PAD) was diagnosed in 101 patients by ABI ≤0.90 and/or by angiography. Traditional cardiovascular risk factors and components of serum fatty acids were examined in all patients (mean age 73.2±0.9 years; 81 males), and compared with those in 373 age- and sex-matched control subjects with no evidence of PAD. RESULTS: The presence of PAD (mean ABI: 0.71±0.02) was independently associated with low levels of gamma-linolenic acid (GLA) (OR: 0.90; 95% CI: 0.85–0.96; P = 0.002), eicosapentaenoic acid∶arachidonic acid (EPA∶AA) ratio (OR: 0.38; 95% CI: 0.17–0.86; P = 0.021), and estimated glomerular filtration rate (OR: 0.97; 95% CI: 0.96–0.98; P<0.0001), and with a high hemoglobin A1c level (OR: 1.34; 95% CI: 1.06–1.69; P = 0.013). Individuals with lower levels of GLA (≤7.95 µg/mL) and a lower EPA∶AA ratio (≤0.55) had the lowest ABI (0.96±0.02, N = 90), while the highest ABI (1.12±0.01, N = 78) was observed in individuals with higher values of both GLA and EPA∶AA ratio (P<0.0001). CONCLUSION: A low level of GLA and a low EPA∶AA ratio are independently associated with the presence of PAD. Specific fatty acid abnormalities and imbalances could lead to new strategies for risk stratification and prevention in PAD patients.